KAJIAN LITERATUR: PENGARUH MERGER DAN AKUISISI TERHADAP KINERJA KEUANGAN PERUSAHAAN - Fadya Nafisah; Mira Choirunnisa; Fadiya ‘Aqila Rahma; Endang Kartini Panggiarti (CV. Denasya Smart Publisher, 2026)
This research aims to describe the impact of mergers and acquisitions on corporate financial performance based on a literature review of previous research. The method used is a qualitative approach through a literature review utilizing secondary data from relevant studies. A total of 25 studies analyzed commonly used financial performance indicators, such as ROA, ROE, CR, DER, DAR, and TATO. The results of the review show that the impact of mergers and acquisitions on company financial performance varies and is inconsistent across industries and observation periods. Several studies found a significant increase in profitability and liquidity, while most other studies showed no significant change in financial ratios after the merger. These findings confirm that the success of mergers and acquisitions is highly dependent on the effectiveness of integration and the internal conditions of the company.